2007
DOI: 10.1111/j.1740-0929.2007.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carcass and meat characteristics of Brahman grade cattle (Bos indicus) and crossbred water buffalo (Bubalus bubalis)

Abstract: This study was conducted to determine and compare the live traits, carcass yield and the physical, chemical, processing and sensory properties of meat from 20 Brahman grade cattle (crossbred cattle) and crossbred water buffalo (Philippine carabao × Murrah, Bulgarian or Indian) with an average age and weight of 29 months and 434 kg, respectively. The animals were fed a similar diet for 180 days before slaughter. A survey was performed to establish consumer meat preference between the two species. Live weights b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
3
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
(10 reference statements)
5
17
3
1
Order By: Relevance
“…In the present experiment, there was no significant gender effect in the results obtained with both species (the crossbred cattle and the crossbred water buffalo), hence the mean values shown in the tables are the mean of 10 animals and standard error of mean was as same as in the previous works (Lapitan et al . 2004a,b, 2007).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…In the present experiment, there was no significant gender effect in the results obtained with both species (the crossbred cattle and the crossbred water buffalo), hence the mean values shown in the tables are the mean of 10 animals and standard error of mean was as same as in the previous works (Lapitan et al . 2004a,b, 2007).…”
Section: Resultssupporting
confidence: 69%
“…In previous study reported by Lapitan et al . (2004a, 2007) the crossbred water buffalo had a comparable production performance in terms of meat production, carcass and meat quality to the crossbred cattle under high grain‐based fattening rations.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Anderson (1975) illustrated that plane of nutrition did not affect muscle and fat yields up to 350 kg and 230 kg BW, respectively, in cattle. More fat (33.3%) and less lean and bone (55.5 and 11.3%) than the present study were found in heavier buffalo males with better planes of nutrition grown at 0.83 kg/day from 340 to 490 kg BW having been fed maize silage, brewers grain and concentrate in 5:3:2 at 3% of BW on a total DM basis (Lapitan et al . 2007).…”
Section: Discussionmentioning
confidence: 38%